Tositumomab and Iodine I 131 Tositumomab (Bexaar) - Srinivasan, A.; Mukherji, S.K. (American Journal of Neuroradiology, 2011)
SUMMARY: Tositumomab and iodine I 131 tositumomab (Bexaar) therapeutic regimen targets monoclonal antibodies against the CD20 antigen expressed in non-Hodgkin lymphoma. This article reviews the mechanism of action and clinical indications for this regimen.